Cardiovascular manifestations of systemic lupus erythematosus: the significance of heart failure - R. A. Karateev (Научно-практическая ревматология)
The involvement of the cardiovascular system is a typical manifestation of systemic lupus erythematosus (SLE), which determines the high level of mortality and disability of patients. A serious clinical problem is the development of heart failure (HF), which frequency in SLE is 3–4 times more than in the population. The development of this pathology is a complex process that occurs under the influence of systemic autoimmune inflammation and associated with heart damage (pericarditis, myocarditis, endocarditis, coronary artery disease, myocardial infarction), disorders of the cardiac conduction system (various arrhythmias), atherosclerosis, arterial hypertension, pulmonary hypertension, thrombosis against connected with bleeding disorders (especially associated with antiphospholipid syndrome), traditional risk factors, as well as the negative effect of anti-rheumatic therapy. Mostly HF in SLE occurs in a subclinical form with a preserved ejection fraction, and is detected using instrumental methods in more than 60% of patients. The management of patients with SLE and HF requires early diagnosis of this pathology, to do this, various diagnostic methods are used (particularly, echocardiography with speckle tracking imaging technique) and the identification of biomarkers such as NT-proBNP. HF therapy in SLE patients is based on the maximal reduction o f the activity of the disease due to rational pathogenetic therapy, also the control of traditional risk factors – antihypertensive therapy, the use of statins and the prevention of arterial and venous thrombosis.